Inhibition of poly(A) polymerase by rifamycin derivatives - Jacob, Samson T. (1974)
The effect of several rifamycin derivatives on poly(A) synthesis in vitro was tested using purified rat liver mitochondrial poly(A) polymerase assayed with an exogenous primer. When used at a concentration of 300 μg/ml, derivatives AF/013, PR/19, AF/AETP, M/88 and AF/ABDP completely inhibited activity corresponding to 50 μg of enzyme protein. Under similar conditions, derivatives DMAO and AF/MO failed to inhibit enzyme activity. Studies with PR/19 showed that the drug interacted directly with the enzyme molecule and did not affect the enzyme-primer complex formation. The inhibition by the drug could be reversed by increasing the substrate (ATP) concentration. It is concluded that some rifamycin derivatives can specifically inhibit template-independent nucleotide chain elongation reactions.